1982
DOI: 10.2307/1938863
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Winter Feeding on Limpets by Black Oystercatchers, Haematopus Bachmani

Abstract: Black Oystercatchers fed on limpets in an intertidal boulder field at a rate of 2 limpets°m—2°yr—1. The birds exert a major influence on the microdistribution of these molluscs. Where accessible to oystercatcher predation, limpets are unlikely to survive over a winter once they reach moderate size (10—14 mm). Collisella pelta are exceptional in having refuge in large size. Oystercatchers thus produce and reinforce patchy limpet distributions. Adaptations of the limpets include crypsis and habitat selection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
99
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(102 citation statements)
references
References 14 publications
3
99
0
Order By: Relevance
“…We note that predators need not necessarily be abundant to affect an impact on prey distribution and abundance, as Frank (1982) has demonstrated relative to oystercatcher predation on intertidal limpets, and as Estes et al (1998) have shown relative to killer whale predation on sea otters. Wooton (1992) has suggested that raccoons preying on sea urchins (Strongylocentrotus spp.)…”
Section: What Are the Ecological And Evolutionary Consequences Of Marmentioning
confidence: 82%
“…We note that predators need not necessarily be abundant to affect an impact on prey distribution and abundance, as Frank (1982) has demonstrated relative to oystercatcher predation on intertidal limpets, and as Estes et al (1998) have shown relative to killer whale predation on sea otters. Wooton (1992) has suggested that raccoons preying on sea urchins (Strongylocentrotus spp.)…”
Section: What Are the Ecological And Evolutionary Consequences Of Marmentioning
confidence: 82%
“…Herbivorous snails and limpets are important components of gull and oystercatcher diets (20,21,25,27), and both are known to significantly reduce fleshy algal cover in the marine rocky intertidal through grazing (21,(27)(28)(29)(30)(31). Therefore, rat predation on the birds indirectly changes the rocky intertidal community from an algal-to an invertebrate-dominated system by releasing intertidal herbivores from predation pressure, which reduces fleshy algal cover via increased herbivory.…”
Section: Rat Infestedmentioning
confidence: 99%
“…Gulls and oystercatchers are groundnesting, year-round residents of the Aleutian Islands, with gulls occurring throughout the archipelago and oystercatchers occurring east of Ϸ176°E (20). They forage extensively in the intertidal, significantly decreasing densities of intertidal invertebrates through predation and indirectly influencing the presence of fleshy algae (21)(22)(23)(24). In the summer, oystercatchers establish combined nesting and feeding territories, thereby foraging in the intertidal near their nesting sites (20), whereas gulls feed almost exclusively in the intertidal starting in mid-July after their young begin to fledge (25).…”
mentioning
confidence: 99%
“…Also, owl limpets can be strongly preyed upon by the American black oystercatcher Haematopus bachmani, a territorial shorebird that can exert sufficient predation pressure to influence limpet abundances and L. gigantea's utilization of microhabitat (Lindberg et al 1987(Lindberg et al , 1998. However, American black oystercatchers are very sensitive to human presence (Sowls et al 1980, Frank 1982, Lindberg et al 1987, 1998 and are essentially absent from heavily populated, urban coastlines.…”
Section: Introductionmentioning
confidence: 99%